2010
DOI: 10.1158/1078-0432.ccr-10-0569
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative CTLA-4 Blockade: Tolerability and Immune Monitoring in the Setting of a Presurgical Clinical Trial

Abstract: Purpose: Cytotoxic T lymphocyte associated antigen (CTLA-4) blockade is being explored in numerous clinical trials as an immune-based therapy for different malignancies. Our group conducted the first preoperative clinical trial with the anti-CTLA-4 antibody ipilimumab in 12 patients with localized urothelial carcinoma of the bladder.Experimental Design: Six patients were treated with 3 mg/kg/dose of anti-CTLA-4 and six patients were treated with 10 mg/kg/dose of antibody. Primary end points of the study were s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
246
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(268 citation statements)
references
References 25 publications
(20 reference statements)
15
246
0
3
Order By: Relevance
“…10 This observation is in line with previous reports showing that this T cell subpopulation was upregulated both in the peripheral blood and at tumor site of MM patients following IPI treatment. 19,22,23,28,[30][31] The evidence that IPI treatment of MM patients can upregulate the frequency in the periphery of memory/activated T cell subsets was also observed in our study. [24][25][26][27][28] Taken together these observations corroborate the hypothesis that changes of the frequency of circulating T cell subsets from patients enrolled in the NIBIT-M1 study resulted from the activity of the checkpoint blockade agent and were not affected by chemotherapy.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…10 This observation is in line with previous reports showing that this T cell subpopulation was upregulated both in the peripheral blood and at tumor site of MM patients following IPI treatment. 19,22,23,28,[30][31] The evidence that IPI treatment of MM patients can upregulate the frequency in the periphery of memory/activated T cell subsets was also observed in our study. [24][25][26][27][28] Taken together these observations corroborate the hypothesis that changes of the frequency of circulating T cell subsets from patients enrolled in the NIBIT-M1 study resulted from the activity of the checkpoint blockade agent and were not affected by chemotherapy.…”
Section: Discussionsupporting
confidence: 86%
“…2,17,18 Along this line, the increase of the absolute leukocyte cell count (ALC) or of circulating CD4 C T cells expressing the inducible co-stimulatory molecule (ICOS) have been documented in relation with anti-CTLA-4 mAb therapies. 12,[19][20][21] ICOS C T cells that were augmented by IPI therapy in tumor lesions from prostate cancer patients, represented lymphocytes endowed with antitumor activity. 22,23 Moreover, increased levels in the periphery of central memory or effector memory CD4 C and CD8 C T cells have been described in patients undergoing IPI treatment, although there was no correlation with the clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these authors correlated the increased and sustained frequency of ICOS hi CD4 C T cell to improved overall survival in an independent cohort of 14 melanoma patients treated with 10 mg/kg ipilimumab. 41 More recently, in a study analyzing 36 patients treated with ipilimumab, an increased frequency of ICOSC CD4 C T cells was proposed as a pharmacodynamic biomarker of CTLA-4 blockade activity at the dose of 3 mg/kg. 26 We were not able to confirm these observations in our cohort of 77 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with ipilimumab significantly increases median overall survival in both previously untreated and treated patients with metastatic melanoma (Hodi et al, 2010). Immune monitoring studies of patients with bladder cancer who were treated with two cycles of preoperative ipilimumab, have shown that treatment with anti-CTLA-4 antibody leads to an increase in the population of CD4+ inducible costimulator cells (CD4+ICOShi) in both tumor tissues and peripheral blood (Carthon et al, 2010). The preliminary data also indicated that an increased frequency of CD4+ inducible costimulator cells correlated with increased likelihood of clinical benefit.…”
Section: Targetting Cytotoxic T-lymphocyte Antigen 4 (Ctla-4)mentioning
confidence: 97%